1984
DOI: 10.1111/j.1744-7348.1984.tb05599.x
|View full text |Cite
|
Sign up to set email alerts
|

Floral biology and pollen viability of parental lines of onion hybrids

Abstract: SUMMARYParental lines (inbred and hybrid male‐sterile lines and inbred pollinators) of prospective F, hybrids from the NVRS spring‐sown bulb onion breeding programme were examined to study their floral biology and aspects of pollination under glasshouse conditions. Inbreeding depression occurred in both pollinator and male‐sterile inbreds in terms of reduced flower numbers per umbel and a greater proportion of defective pistils. Male‐sterile and male‐fertile lines differed in their stigma and style characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
3

Year Published

1984
1984
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
4
0
3
Order By: Relevance
“…The correlation between the percentage of stainable pollen and germination was significant (P < 0.001), although it was only 0.45. Other researchers have reported low correlations between pollen germination and stainability using acetocarmine, cotton blue, or fluorescein diacetate (Ali et al, 1984;Gates, 1976a, 1976b). Overall, these previous studies reported pollen germination rates of 50% or less, and it is not clear if the low germination was due to the medium type, amounts of sucrose and/or microelements, or other factors (Gomes et al, 2000;Ockendon and Gates, 1976a).…”
Section: Resultsmentioning
confidence: 96%
“…The correlation between the percentage of stainable pollen and germination was significant (P < 0.001), although it was only 0.45. Other researchers have reported low correlations between pollen germination and stainability using acetocarmine, cotton blue, or fluorescein diacetate (Ali et al, 1984;Gates, 1976a, 1976b). Overall, these previous studies reported pollen germination rates of 50% or less, and it is not clear if the low germination was due to the medium type, amounts of sucrose and/or microelements, or other factors (Gomes et al, 2000;Ockendon and Gates, 1976a).…”
Section: Resultsmentioning
confidence: 96%
“…A média de flores por umbela registrada na literatura é variável, a exemplo de 612,2 para Crioula em Santa Catarina (Müller & Casali 1982) e de outras cultivares híbridas que apresentaram de 213 a 485 flores por umbela (Currah 1981, Ali et al 1984e Lorenzon & Almeida 1993.…”
Section: Resultsunclassified
“…De acordo com outros autores, a duração do episódio de floração em uma umbela pode variar de 16 a 35 dias (Currah & Ockendon 1978, Ali et al 1984, Acosta et al 1993.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…and is greatly affected by environment, age and the position within the plant [25]. In KP onion, floral differentiation and organogenesis occur simultaneously with both scape elongation and vegetative growth and development as reported in other varieties of onion [7].…”
Section: Resultsmentioning
confidence: 99%